Case report: Clinical profile, molecular genetics, and neuroimaging findings presenting in a patient with Kearns-Sayre syndrome associated with inherited thrombophilia - Gogu, Anca Elena; Jianu, Dragos Catalin; Parv, Florina; Motoc, Andrei Gheorghe Marius; Axelerad, Any; Stuparu, Alina Zorina; Gogu, Andreea Alexandra (Frontiers in Neurology, 2024)
Background Kearns-Sayre syndrome (KSS) is classified as one of the mitochondrial DNA (mtDNA) deletion syndromes with multisystemic involvement. Additionally, the negative prognosis is associated with inherited thrombophilia, which includes the presence of homozygous Factor V G1691A Leiden mutation, MTHFR gene polymorphisms C677T and A1298C, and PAI-1 675 homozygous genotype 5G/5G. Case presentation This case report presents a 48-year-old man with chronic progressive external ophthalmoplegia, bilateral ptosis, cerebellar ataxia, cardiovascular signs (syncope, dilated cardiomyopathy, and cardiac arrest) with electrocardiographic abnormalities (first-degree atrioventricular block and major right bundle branch block), endocrine dysfunction (short stature, growth hormone insufficiency, primary gonadal insufficiency, hypothyroidism, and secondary hyperparathyroidism), molecular genetic tests (MT-TL2 gene), and abnormal MRI brain images, thus leading to the diagnosis of KSS. The patient came back 4 weeks after the diagnosis to the emergency department with massive bilateral pulmonary embolism with syncope at onset, acute cardiorespiratory failure, deep left femoral-popliteal vein thrombophlebitis, and altered neurological status. In the intensive care unit, he received mechanical ventilation through intubation. Significant improvement was seen after 2 weeks. The patient tested positive for inherited thrombophilia and was discharged in stable conditions on a new treatment with Rivaroxaban 20 mg/day. At 6 months of follow-up, ECG-Holter monitoring and MRI brain images remained unchanged. However, after 3 months, the patient died suddenly while sleeping at home. Conclusion The genetic tests performed on KSS patients should also include those for inherited thrombophilia. By detecting these mutations, we can prevent major complications such as cerebral venous sinus thrombosis, coronary accidents, or sudden death.